Dialectal Comparison between Muaro Takung and Maloro Sub-Dialect: The Lexical Variation - Monica Rahma Putri; Jufrizal Jufrizal (Universitas Negeri Padang, 2023)
Language evolves over time and varies depending on location and social context. The lexical variation in speaking is influenced by several factors, including age, education level, and linguistic competence. This research is about lexical variation. The goal of this study is to distinguish the lexical differences between Muaro Takung and Maloro sub-dialects and to count the percentage of lexical differences between those two sub-dialect . So it can be concluded that Muaro Takung and Maloro are dialects, sub-dialects, or just speak differences. The data of this reseach was 258 words taken from 205 swadesh list and 53 from basic vocabularies used in everyday conversations. The data was collected from ten informants with specific categories. Furthermore, this research used dialectometric formula to count the percentage of the lexical differences between Muaro Takung and Maloro sub-dialect. From the data, the researcher found the lexical differences between Muaro Takung sub-dialect and Maloro sub-dialect and categorized it into seven types, noun, verb, adjective, pronoun, determiner, subordinate conjunction and preposition. The calculation of the percentage of lexical differences shows Muaro Takung is 25,9% and Maloro is 35,3%.